Unlocking English-Medium Instruction (EMI) Success: Exploring Language–Content Teacher Collaboration for Enhanced Learning in Bilingual Classrooms - Yulianti, Dwiana Binti; Maghfiroh, Ana; Sugianto, Alip; Rokhaniyah, Hesti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to identify the forms of collaboration between content and language teachers in EMI, examine the challenges they encounter, and proposes strategies to enhance effective cooperation. Using a qualitative case study design, data were collected through semi-structured interviews and focus group discussions with teachers at Sekolah Dasar Muhammadiyah Terpadu Ponorogo. The data analysis technique in this study employed an interactive model consisting of data reduction, data display, and conclusion formulation or verification. Findings reveal that collaboration takes place mainly during lesson preparation, where content teachers ensure the accuracy of disciplinary concepts while English teachers simplify and scaffold the language for student comprehension. However, teachers face difficulties in balancing linguistic simplicity with subject accuracy, the limited availability of bilingual teaching resources, and diverse levels of student motivation. To address these challenges, teachers employ strategies such as scaffolding, repetition, curriculum adjustment, parental involvement, and differentiated support. These practices highlight the dual role of English teachers as both language and subject instructors and the advisory role of content teachers in safeguarding content precision. The study concludes that effective bilingual education depends on structured collaboration, adaptive pedagogy, and continuous professional development. The findings suggest school should mandate weekly co-planning and offer focused training on content-language integration in EMI classroom.